Integrated Valorization of Malagasy Micro-Crustaceans : Caridina Serratirostris, Caridina Typus and Acetes Erythraeus for the Blue Circular Economy - Fifaliana, Rasolofoson Joharisoa; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
Chronic malnutrition in Madagascar's Haute Matsiatra region is linked to severe deficits in animal protein and micronutrients. This study evaluates the nutritional composition and market dynamics of three indigenous micro-crustacean species (collectively known as patsa or chevaquine) for sustainable valorization within a Blue Circular Economy framework.Nutritional analysis established the Red Shrimp (Caridina serratirostris) as a superior functional food. It possesses extraordinary density of critical nutrients, including 46,174 ppm of Calcium and an unparalleled 5,360 ppm of Iron (Fe was undetectable in other varieties). Furthermore, its high 22.37 % Lipid content makes it a crucial calorie-dense resource, yielding 1,607.8 kcal/100 g. Market data from Anjoma Market indicated a high-value, high-demand profile for the Red Shrimp, but also significant supply chain fragility. In contrast, the White Shrimp (Acetes erythraeus), despite low market value, showed greater commercial stability, with up to 5.4 % of vendors selling 10 to 50 kg/day. The proposed valorization strategy is two-tiered: The limited, high-value Red Shrimp supply should be dedicated to nutritional powder fortification, while the higher-volume White Shrimp should be directed toward aquaculture feed concentrates. Overcoming pervasive constraints—especially the high > 88 % Moisture content and lack of cold storage—mandates the immediate deployment of localized solar drying technologies to transform this biomass into stable, high-value ingredients.